The Effect of Interest Rates, Inflation, and Exchange Rates on Stock Prices of Companies Listed on The Jakarta Islamic Index (JII) - Muhammad Farid; Muhammad Agus Mujadi (Muhasabatuna : Jurnal Akuntansi Syariah, 2026)
Stock prices in the real market are highly dynamic closing prices and can change quickly due to the volume of supply and demand in the capital market. This quantitative research aims to examine the influence of macroeconomic factors consisting of interest rates ($X_1$), inflation ($X_2$), and exchange rates ($X_3$) on stock prices ($Y$). The research subjects were companies listed on the Jakarta Islamic Index (JII) for the period 2021-2024. Using a purposive sampling method, a sample of 25 companies was obtained with a total of 100 observations over four years. The data analysis technique used was multiple linear regression analysis with the assistance of SPSS software. The results of the data analysis indicate that, partially, interest rates have no positive and insignificant effect on stock prices. Meanwhile, inflation and exchange rates have been shown to have a positive and significant effect on the stock prices of companies listed on the Jakarta Islamic Index (JII).